The Influence of Pre-Match Logical Stimulus for Applying and Developing Strategy to Basketball Team of Faculty of Medicine Universitas Padjadjaran - Razif Fiil Ikhlas; Vita Muniarti Lubis; Vitriana Vitriana (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Logical game is rarely used in sport program as a menu for athletes to prepare their condition in pre-match to improve their cognitive performance. The athletes who have good cognitive performance can think, analyze and solve the problem appeared. Griffith builds a method to improve the athletes’ performance by stimulating their cognitive resources. This study aimed to know the influence of pre-match logical stimulus in applying and developing strategy in basketball players.Methods: The subject of this study was the basketball team players of Faculty of Medicine Universitas Padjadjaran; they were chosen by total sampling based on inclusion and exclusion criteria. Then, they were divided into two groups randomly: control and exposed groups. Both groups will be compared based on the score of each item (in total of 17 items). The assessed items were technique and tactics in the game of basketball. This study was conducted in November 2012 for three weeks. The collected data were analyzed using paired-T test.Results: Score increased significantly (p<0.05) in all items for first to third from four times of data retrieval in the exposed group, whereas in the control group, score decreased significantly (p<0.05) in all items for first to third from four times of data retrieval.Conclusions: Pre-match logical stimulus can improve the performance, especially technique and tactic in the basketball game. DOI: 10.15850/amj.v2n3.480